Effectiveness and tolerability of perampanel monotherapy in children with newly diagnosed focal epilepsy - Zhao, Fen; Ren, Ying; Geng, Guifu; Zhang, Tong; Hu, Wandong; Zhang, Huan; Jin, Ruifeng; Shi, Jianguo; Gao, Zaifen; Zhang, Hongwei; Liu, Yong (Frontiers in Neurology, 2023)
Objective To examine the clinical effectiveness and tolerability of perampanel (PER) as initial monotherapy in pediatric patients with newly diagnosed focal epilepsy. Methods A retrospective analysis was conducted on 62 children with newly diagnosed focal epilepsy who were treated with PER at the Epilepsy Center of Jinan Children's Hospital from July 2021 to July 2022. The treatment status, prognosis, and adverse reactions were followed up for a minimum of 6 months after the initiation of PER monotherapy. The effectiveness of the patients was estimated by the PER effective rate at 3-, 6-, and 12-month follow-up evaluations and adverse reactions were also recorded. The effective rates of PER in different etiologies and epilepsy syndromes were also statistically analyzed. Results The effective rates of PER treatment at the different time points of evaluation were 88.7% (3 months), 79.1% (6 months), and 80.4% (12 months). With PER treatment, seizure freedom varied over time, with 61.3%, 71.0%, and 71.7% of patients at the 3-, 6-, and 12-month follow-ups, respectively. Among the etiologies of epilepsy, the effective rates of genetic etiology, structural etiology, and unknown etiology were generally above 50% at the 3-, 6-, and 12-month follow-ups. Among the epilepsy syndromes, the categories with higher treatment efficacy were self-limiting epilepsy with centrotemporal spikes (SeLECTs), self-limited epilepsy with autonomic seizures (SeLEAS), and childhood occipital visual epilepsy (COVE), with an effective rate of above 80%. Adverse events were documented in 22 patients (35.5%), but they were mild and tolerable. The most common adverse events comprised irritability, drowsiness, dizziness, and increased appetite. Conclusion PER has favorable effectiveness and tolerability as initial monotherapy for children with newly diagnosed focal epilepsy, which could be a potential option for long-term medication in the treatment of focal epilepsy in children. The current study provided potential evidence for PER as initial monotherapy in children with focal epilepsy in clinical practice.